Rekonstruksi Kurikulum Berorientasi Outcome dalam Era Society 5.0: Integrasi Literasi Digital, Keterampilan Abad 21, dan Pembelajaran Adaptif - Fien Pongpalilu; Dewi Nopitasari; Rampeng Rampeng (Published by Institut Teknologi Pendidikan Indonesia, 2026)
This research aims to examine the reconstruction of outcome-oriented curriculum in the era of Society 5.0 through the integration of digital literacy, 21st century skills, and adaptive learning. The Society 5.0 era requires the education system to produce students who not only master knowledge, but also are able to think critically, creatively, collaboratively, communicatively, adaptively, and use technology ethically and productively. This research uses a literature research method by examining various literature, scientific articles, books, and policy documents relevant to Outcome-Based Education, Society 5.0, digital literacy, 21st century skills, and adaptive learning. The results of the study show that an outcome-oriented curriculum needs to be designed based on learning outcomes that are clear, measurable, and relevant to future needs. Digital literacy integration plays a role in building students' ability to access, evaluate, process, and create digital information. 21st century skills strengthen problem-solving, communication, collaboration, and innovation skills, while adaptive learning supports a learning process that suits learners' needs and abilities. Thus, the reconstruction of the outcome-oriented curriculum is an important strategy in building education that is relevant, humanist, flexible, and responsive to the challenges of the Society 5.0 era